ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKADEMIK PADA STIKES PRIMA JAMBI - Siagian, Saut Horas Tua; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2018)
Currently the management of Academic data on STIKes Prima Jambi Jambi there are still some obstacles even STIKes Prima Jambi has been using the computer as a data processor by utilizing microsoft excel application. However, the recorded data are not mutually related to each other to enable duplicate content in the data held. In addition, the use of the internet as a medium of information to students is still not effective. So that students in getting academic information still have to manual, for example if want to see value still have to come to campus and look at bulletin board. KRS filling is still manual on a KRS form. So that the web owned is still not optimally used